Media history worldviews and communication futures - Ahmad Murad Merican (University of Malaya Press, 2005)
This book is a result of an ongoing study, having its genesis nine years ago when the author was doing his doctoral dissertation at the University Malaya. This book provides a different treatment and direction to the subject, with materials substantially revised and expanded from five out of nine chapters (four chapters have been omitted)